TASMI' METHOD AND ITS IMPACT ON QUALITY MEMORIALIZATION OF THE AL-QUR'AN - Mufidah, Elmi; Aisyah, Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research discusses the use of the tasmi’ (listen and repeat) in the context of teaching tahfidz Al-Qur'an at Pondok Nurul Jadid Islamic Boarding School, Al Mawaddah area. The main aim of the research This is to analyze the impact of the tasmi’ on quality memorization of the Al-Qur'an by students. A qualitative approach is used for understand the experiences and perceptions of students regarding this method. Study involving participants from among the students of the Nurul Islamic Boarding School Jadid has followed the tahfidz process using the tasmi method. Data was collected through participant observation, in-depth interviews, and analysis of related documents. The research results show that tasmi method' has a positive impact on the quality of memorizing Al- The Qur'an, allows for a deeper understanding of the meaning and recitation deep. The research involved participants from Pondok students Nurul Jadid Islamic Boarding School which has followed the tahfidz process uses tasmi method'. Data was collected through participant observation, in-depth interviews, and analysis of related documents. Research result shows that the tasmi’ have a positive impact on the quality of memorizing the Qur'an, enabling understanding of the meaning and deeper recitation.